Is Variation in Biological and Residential Ties to Children Linked to Mothers' Parental Stress and Perceptions of Coparenting?. (March 2019) - Guzzo, Karen Benjamin; Hemez, Paul; Anderson, Lydia; Manning, Wendy D.; Brown, Susan L.
Mothers with children from prior relationships or with stepchildren may perceive greater challenges in parenting than their counterparts in less complex families. We use the Families and Relationships Study to analyze parental stress and perceptions of coparenting among cohabiting and married mothers with resident minor children ( N = 679). Compared with mothers with only shared children, parental stress and perceptions of coparenting generally do not differ when mothers have children from prior unions. However, mothers with resident stepchildren evaluate the distribution of child care as less fair, consider their partners as less reliable coparents, and rate their partner more poorly as a coparent relative to those with no stepchildren. These findings suggest that creating a stepfamily through one's own children may not present additional parenting challenges or stressors, whereas having stepchildren introduced through a partner may be linked to a different, and less positive, parenting experience.